(untitled) (Praxis Educativa, 2023)
This article presents, analyzes and reconstructs the educational status of women deprived of their liberty in Penal Unit No. 2 of the Province of Catamarca. The focus is placed on the process of institutionalization of schooling in 2014, which produced a break with respect to the situation that this sector of the population found previously, that is, on the edges of the school. Likewise, we try to give an account of the local particularities that were presented between the school and the penitentiary, in the organizational aspects, the operating dynamics and the forms of deployment that are developed. We believe that it is essential in our study to pay attention to both the teaching work and the participation of the students of a school in permanent reinvention, open to constant disruptions and the uncertainty generated by moving through a non-regular daily life in the ways of inhabiting the school.